Gabay sa primary health care para sa mga punong barangay - Bautista, Victoria A. (Community Health Service, Department of Health, 1998)
This manual answers the questions of the local chief executives about primary health care and their role on its implementation. It is intended to teach the community and its leaders to be aware about primary health care towards the advancement of health.